An Investigation of the Student's Reading Comprehension Difficulties at Ma Al - Muslimun NWDI Tegal Meninting, Batulayar, Lombok Barat - Jumadil; Sukarni, Sri; Aprionoto (Arus Jurnal Sosial dan Humaniora, 2024)
The purpose of this study was to determine the most difficult aspects of reading comprehension, especially in descriptive texts experienced by class X students of MA AL Muslimun NWDI Tegal and the factors that cause these difficulties. This study uses a qualitative method, where tests and interviews are used as instruments in data collection. The subjects of this study were class X students of MA AL Muslimun NWDI Tegal Sigi in the 2024/2025 academic year. The test was given to 10 students and consisted of 15 questions divided into five types of questions, namely main ideas, finding references, understanding vocabulary, making conclusions, and detailed information. Then, the researcher interviewed 5 students by giving them 10 questions. The test results showed that the most difficult aspects faced by class X students of MA AL Muslimun NWDI were understanding long sentences, understanding main ideas, understanding grammar, in concluding the contents of vocabulary text readings. While the findings of the interviews, however, indicated that both internal and external variables contributed to students' challenges in comprehending texts. Lack of reading methods, a small vocabulary, and little student motivation are internal issues. The environment of the learner is an example of an external component.